2010
DOI: 10.3892/etm.2010.163
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antitumor activities of water extracts from the root of Actinidia kolomikta

Abstract: Abstract. the genus of Actinidia is widely distributed throughout the Asian continent. Specific Actinidia species have been used as health foods and medical products for cancer treatment. Actinidia kolomikta is a species of wild plant that grows in the northern part of indochina. however, few studies on its bioactivity have been reported. in this study, the polysaccharide and polyphenol contents, the SOd-like activity and the dpph radical-scavenging activity of water extracts from the root of Actinidia kolomik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…In comparison, the TPC in the leaves and stems of kiwiberry cultivars was found to be 4-and 2-fold higher, respectively, than those in widely recognized medicinal plants and functional foods, such as Angelica gigas, Morus alba, and red ginseng [36]. However, the methanol extract of Actinidia kolkmikta roots demonstrated a TPC of 201.9 mg GAE•g −1 , which is 20-fold higher than that observed in A. arguta in our study, suggesting that different extraction methods potentially influence the concentrations detected [37]. Our study was the first to compare the TPC and TFC in vegetative tissues of different kiwiberry cultivars and found that they all contain high levels of TPC and TFC, suggesting significant potential for their use in functional and medicinal products.…”
Section: Total Phenolic and Flavonoid Content In Vegetative Tissues O...contrasting
confidence: 79%
“…In comparison, the TPC in the leaves and stems of kiwiberry cultivars was found to be 4-and 2-fold higher, respectively, than those in widely recognized medicinal plants and functional foods, such as Angelica gigas, Morus alba, and red ginseng [36]. However, the methanol extract of Actinidia kolkmikta roots demonstrated a TPC of 201.9 mg GAE•g −1 , which is 20-fold higher than that observed in A. arguta in our study, suggesting that different extraction methods potentially influence the concentrations detected [37]. Our study was the first to compare the TPC and TFC in vegetative tissues of different kiwiberry cultivars and found that they all contain high levels of TPC and TFC, suggesting significant potential for their use in functional and medicinal products.…”
Section: Total Phenolic and Flavonoid Content In Vegetative Tissues O...contrasting
confidence: 79%
“…studies verified that the plant produces a variety of glycosides, flavonoids, polyphenols, sterols, triterpenoids, organic acids, and vitamin C (Chesoniene et al 2004;Zuo et al 2012). Recent pharmacological studies have reported that an extract of A. kolomikta possessed several biological properties, including antioxidant, anti-tumor, anti-proliferative, anti-allergy, and anti-hyperglycemic activities (Guan et al 2011;Zuo et al 2012;Hu et al 2015). Although many pharmacological activities have been reported, the components responsible for the anti-inflammatory properties have not yet been identified.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 96%